Activity, specificity, and titer of naturally occurring canine anti–DEA 7 antibodies. (November 2016) - Spada, Eva; Proverbio, Daniela; Baggiani, Luciana; Canzi, Ilaria; Perego, Roberta
The reported prevalence of naturally occurring anti–dog erythrocyte antigen (DEA) 7 antibodies in DEA 7–negative dogs is as high as 50%. Characterization of these antibodies may better define their importance in canine transfusion medicine. We determined in vitro activity, specificity, and titer of anti–DEA 7 antibodies in DEA 7–negative dogs. Plasma samples from 317 DEA 7–negative dogs were cross-matched with DEA 7–positive red blood cells (RBCs) using gel column technology. Agglutination occurred with DEA 7–positive RBCs but not with DEA 7–negative RBCs in 73 samples (23%), which were hence classified as containing anti–DEA 7 antibodies. These samples were evaluated for hemolytic and agglutinating activity, strength of agglutination, and antibody specificity and titers. All samples showed agglutination but none showed hemolysis. Gel agglutination was graded as 1+ for 20 samples (27%), 2+ for 49 samples (67%), 3+ for 4 samples (6%); no samples were graded 4+. The agglutination titer was <1:2 for 51 samples (73%), 1:2 for 13 samples (19%), 1:4 for 4 samples (5%), and 1:8 for 2 samples (3%). Of 16 samples treated with 2-mercaptoethanol, 11 samples (69%) contained only IgM, 4 samples (25%) exhibited only IgG activity, and 1 sample (6%) had both IgG and IgM activity. Low titers of warm, weakly agglutinating, mostly naturally occurring IgM anti–DEA 7 antibodies were found in 23% of DEA 7–negative dogs. The presence of naturally occurring anti–DEA 7 antibodies suggests that cross-matching of canine blood recipients is advisable, even at first transfusion, to minimize delayed transfusion reactions.